Non-invasive detection of nasopharyngeal carcinoma using saliva surface-enhanced Raman spectroscopy - QIU, SUFANG (Oncol Lett, 2016)
The present study evaluated the use of saliva surface-enhanced Raman spectroscopy (SERS) for the detection of non-invasive nasopharyngeal carcinoma (NPC). SERS measurements were taken from 62 saliva samples, of which 32 were from NPC patients and 30 from healthy volunteers. Notable biochemical Raman bands in the SERS spectra were tentatively assigned to various saliva components. The saliva SERS spectra obtained from the NPC patients and the healthy volunteers were also analyzed by multivariate statistical techniques based on principal component analysis and linear discriminant analysis (PCA-LDA). Significant differences were observed between the saliva SERS spectral intensities for NPC patients and healthy volunteers, particularly at 447, 496, 635, 729, 1134, 1270 and 1448 cm(−1), which primarily contained signals associated with proteins, nucleic acids, fatty acids, glycogen and collagen. The classification results based on the PCA-LDA method provided a relatively high diagnostic sensitivity of 86.7%, specificity of 81.3% and diagnostic accuracy of 83.9% for NPC identification. The results from the present study demonstrate that saliva SERS analysis used in conjunction with PCA-LDA diagnostic algorithms possesses a promising clinical application for the non-invasive detection of NPC.